The proactivity of academic elites: a systematical approach to proactive behavior development in university settings - Wu, Mingchang; Siswanto, Ibnu; Ko, Chenju; Minghat, Asnul Dahar; Mustakim, Siti Salina (Istanbul Kultur University, 2018)
Proactivity positively moderates the relationship between individuals’ psychological strain and their performance. Proactive personality development becomes a crucial issue for academia in a university setting typically while they encounter high pressure, workload, and challenges resulting from social high expectation of academic exploration and pioneering knowledge. This paper systematically reviews the current phenomena of elites in Taiwan and the emerging needs of proactivity to deal with increasing competition in current environments. Furthermore, it constructively proposes three approaches including self-starting as the internal approach as well as supportive environment building and purposive training program development as external approaches, so that faculty members’ proactivity can be constructed and enhanced. Faculty members’ academic achievement can be promoted according to their proactivity enhancement.